Precise Measurement of the Top-Quark Mass from lepton plus jets Events - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Kirsch, M.; et al. (Amer Physical Soc, 2008)
We measure the mass of the top quark using top-quark pair candidate events in the lepton+jets channel from data corresponding to 1 fb(-1) of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron collider. We use a likelihood technique that reduces the jet energy scale uncertainty by combining an in situ jet energy calibration with the independent constraint on the jet energy scale (JES) from the calibration derived using photon+jets and dijet samples. We find the mass of the top quark to be 171.5 +/- 1.8(stat.+JES)+/- 1.1(syst.) GeV.